Markers of Biological Stress and Mucosal Immunity during a Week Leading to Competition in Adolescent Swimmers. (12th June 2014) - Papadopoulos, E.; Muir, C.; Russell, C.; Timmons, B. W.; Falk, B.; Klentrou, P.
Abstract : In this study we examined changes in the salivary concentrations of immunoglobulin A (sIgA), cortisol (sC), testosterone (sT), and testosterone-to-cortisol ratio (T/C) in 21 competitive swimmers, 11–15 years old, during a week leading to competition as compared to a control (noncompetition) week. No day-to-day changes or significant differences between weeks were observed for sIgA (47.9 ± 4.4 versus 54.9 ± 5.2   μ g/mL for control versus competition week, resp.), sC (2.7 ± 0.2 versus 2.5 ± 0.2  ng/mL for control versus competition week, resp.), and T/C ratio (83.4 ± 7.0 versus 77.9 ± 7.7 for control versus competition week, resp.). In contrast, sT was significantly lower during the week of competition (154.5 ± 11.3  pg/mL) as compared to the control week (181.3 ± 11.5  pg/mL) suggesting that the swimmers were in a catabolic state, although this did not have a negative effect on their performance. In conclusion, salivary cortisol did not change between the two weeks, and thus competition stress was relatively low, and mucosal immunity was unaffected in these young athletes prior to competition.